2023
DOI: 10.1101/2023.04.17.537199
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using rare genetic mutations to revisit structural brain asymmetry

Abstract: Asymmetry between the left and right brain is a key feature of brain organization. Hemispheric functional specialization underlies some of the most advanced human-defining cognitive operations, such as articulated language, perspective taking, or rapid detection of facial cues. Yet, genetic investigations into brain asymmetry have mostly relied on common variant studies, which typically exert small effects on brain phenotypes. Here, we leverage rare genomic deletions and duplications to study how genetic alter… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 132 publications
1
0
0
Order By: Relevance
“…Specifically, both classes of CNVs were linked to adverse impacts on family well-being, as seen in the adverse effects on cognitive functioning, mental health, and socioeconomic outcomes. Our results also highlight the similar ramifications for cognition and behavior associated with deletions and duplication despite their distinct effects on brain anatomy, corroborating some of our earlier CNV-imaging studies on the UK Biobank 8,27 . Finally, we demonstrated that different genomic characteristics drive these shifts in behavior differentiation and brain maturation.…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, both classes of CNVs were linked to adverse impacts on family well-being, as seen in the adverse effects on cognitive functioning, mental health, and socioeconomic outcomes. Our results also highlight the similar ramifications for cognition and behavior associated with deletions and duplication despite their distinct effects on brain anatomy, corroborating some of our earlier CNV-imaging studies on the UK Biobank 8,27 . Finally, we demonstrated that different genomic characteristics drive these shifts in behavior differentiation and brain maturation.…”
Section: Discussionsupporting
confidence: 89%